Treatment of a wide-necked aneurysm of the anterior cerebral artery using two Enterprise stents in “Y”-configuration stenting technique and coil embolization: a technical note - Rohde, Stefan; Bendszus, Martin; Hartmann, Marius; Hähnel, Stefan (Neuroradiology, 2010)
The endovascular treatment of wide-necked aneurysms remains challenging. The “Y”-stenting technique has been used for stent-assisted coil embolization of wide-necked bifurcation aneurysms. So far, this technique has been described for aneurysms of the basilar apex or the middle cerebral artery bifurcation and only for open stent systems using the Neuroform stent. We report a 52-year-old woman with recurrence of a wide-necked aneurysm of the anterior cerebral artery that was successfully retreated by stent-assisted coiling using the “Y”-stenting technique with the Enterprise stent system.